2019
DOI: 10.1126/scirobotics.aav1560
|View full text |Cite
|
Sign up to set email alerts
|

When a robot teaches humans: Automated feedback selection accelerates motor learning

Abstract: A multitude of robotic systems have been developed to foster motor learning. Some of these robotic systems featured augmented visual or haptic feedback, which was automatically adjusted to the trainee’s performance. However, selecting the type of feedback to achieve the training goal usually remained up to a human trainer. We automated this feedback selection within a robotic rowing simulator: Four spatial errors and one velocity error were considered, all related to trunk-arm sweep rowing set as the training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…In recent years, developments on computer processing capabilities, and robotic systems have given rise to robot-assisted training in many fields, e.g., in rehabilitation (Marchal-Crespo and Reinkensmeyer, 2009), in sports simulation (Rauter et al, 2019) and in surgical training (Enayati et al, 2018). Such robotic systems used in various domains share the common purpose of supporting humans improving/acquiring new skills.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, developments on computer processing capabilities, and robotic systems have given rise to robot-assisted training in many fields, e.g., in rehabilitation (Marchal-Crespo and Reinkensmeyer, 2009), in sports simulation (Rauter et al, 2019) and in surgical training (Enayati et al, 2018). Such robotic systems used in various domains share the common purpose of supporting humans improving/acquiring new skills.…”
Section: Introductionmentioning
confidence: 99%
“…Novice participants were observed to benefit from haptic error reduction in golf (Duarte and Reinkensmeyer, 2015), haptic guidance in tennis (Marchal-Crespo et al, 2013), and various unimodal as well as multimodal feedback designs in a complex rowing task (Rauter et al, 2015;Sigrist et al, 2015). Naïve participants' motor learning was also investigated by adapting the provided feedback to the participants' performance in the rowing task (Rauter et al, 2019). The study successfully showed the benefits of automated and individualized feedback selection for beginners; however, further investigation is needed to extend the findings to more advanced participants.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous studies on the rowing simulator, the vibration problem could be suppressed by setting the minimum rope tension force (τ min rope ) to a fixed value of 50 N , since the rendered forces at the end-effector were low due to the fact that body-arm rowing was used as the rowing task [24][25][26][27]. However, this minimum rope tension of 50 N yielded neither realistic recovery forces nor eliminated the transversal vibration issue for the rapid, full-body rowing movement.…”
Section: Control Of Rope Tension Forces During Recoverymentioning
confidence: 99%
“…Although commercial products, which can provide propulsion forces and oar kinematics while rowing on a boat, are available, these devices are not yet capable of providing feedback about the resulting errors, i.e., difference between desired and actual performance [49,50]. Therefore, as previously studied with beginner rowers, three modalities rendered on the rowing simulator could also be used to present feedback to the expert rowers for performance enhancement [26,51,52].…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation